Pengembangan Asesmen Formatif Berbasis Wordwall pada Materi Perkalian Kelas IIIB SDN 66 Kecamatan Pontianak Kota: Penelitian - Dian Sari Juliana Sitompul; Yosterpani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop a Wordwall-based formative assessment for multiplication material for grade III B of SD Negeri 66, Pontianak City District. The background of the study stems from the need for innovative and enjoyable assessments, considering that formative assessments used by teachers tend to be monotonous and have not utilized digital technology. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The resulting product is an interactive formative assessment using the Wordwall application. Validation was carried out by media experts and material experts. The validation results showed a very high level of validity with an average of 95% from media experts and 93% from material experts. Limited trials through teacher and student response questionnaires also obtained a